Monitoring oral health of people in Early Intervention for Psychosis (EIP) teams: the extended Three Shires randomised trial - Adams, Clive E.; Wells, Nicola Clark; Clifton, Andrew; Jones, Hannah; Simpson, Jayne; Tosh, Graeme; Callaghan, Patrick; Liddle, Peter; Guo, Boliang; Furtado, Vivek; Khokhar, Mariam A.; Aggarwal, Vishal. R. (Elsevier, 2018)
Background: The British Society for Disability and Oral Health guidelines made recommendations for oral health care for people with mental health problems, including providing oral health advice, support, promotion and education. The effectiveness of interventions based on these guidelines on oral health-related outcomes in mental health service users is untested. Objective:To acquire basic data on the oral health of people with or at risk of serious mental illness. To determine the effects of an oral health checklist in routine clinical practice. Design: Clinician and service user-designed cluster randomised trial. Settings and Participants: The trial compared a simple form for monitoring oral health care with standard care (no form) for outcomes relevant to service use and dental health behaviour for people with suspected psychosis in Mid and North England. Thirty-five teams were divided into two groups and recruited across 2012-3 with one year follow up. Results: 18 intervention teams returned 882 baseline intervention forms and 274 outcome sheets one year later (31%). Control teams (n=17) returned 366 baseline forms. For the proportion for which data were available at one year we found no significant differences for any outcomes between those allocated to the initial monitoring checklist and people in the control group (Registered with dentist (p=0.44), routine check-up within last year (p= 0.18), owning a toothbrush (p= 0.99), cleaning teeth twice a day (p=0.68), requiring urgent dental treatment (p=0.11). Conclusion: This trial provides no clear evidence that Care Co-ordinators (largely nursing staff) using an oral health checklist improves oral health behaviour or oral health state in those thought to be at risk of psychosis or with early psychosis.